import algebra.group open algebra variables {A : Type} variables [s : group A] include s namespace foo set_option blast.strategy "ematch" attribute inv_inv mul.left_inv mul.assoc one_mul mul_one [forward] theorem mul.right_inv (a : A) : a * a⁻¹ = 1 := calc a * a⁻¹ = (a⁻¹)⁻¹ * a⁻¹ : by blast ... = 1 : by blast theorem mul.right_inv₂ (a : A) : a * a⁻¹ = 1 := by blast theorem mul_inv_cancel_left (a b : A) : a * (a⁻¹ * b) = b := calc a * (a⁻¹ * b) = a * a⁻¹ * b : by blast ... = 1 * b : by blast ... = b : by blast theorem mul_inv_cancel_left₂ (a b : A) : a * (a⁻¹ * b) = b := by blast theorem mul_inv (a b : A) : (a * b)⁻¹ = b⁻¹ * a⁻¹ := inv_eq_of_mul_eq_one (calc a * b * (b⁻¹ * a⁻¹) = a * (b * (b⁻¹ * a⁻¹)) : by blast ... = 1 : by blast) theorem eq_of_mul_inv_eq_one {a b : A} (H : a * b⁻¹ = 1) : a = b := calc a = a * b⁻¹ * b : by blast ... = 1 * b : by blast ... = b : by blast -- This is another theorem that can be easily proved using superposition, -- but cannot to be proved using E-matching. -- To prove it using E-matching, we must provide the following auxiliary step using calc. theorem eq_of_mul_inv_eq_one₂ {a b : A} (H : a * b⁻¹ = 1) : a = b := calc a = a * b⁻¹ * b : by blast ... = b : by blast end foo